Empirics of Solow growth model in Nepali economy - Paudel, Ramesh Kumar (Management Dynamics, 2020)
Economic growth model developed by R. M. Solow explained the steady-state equilibrium in long run based on neoclassical production function with factor substitutions and diminishing returns in context of developed economy. As the nature of Nepali economy is different than developed economy, this paper aims to analyze economic growth of Nepal in the Solow growth model standard. Specifically, it aims to examine the effect of saving rate, labor growth and human capital on economic growth. On basis of steady-state equilibrium equation developed by Solow, regression equation is developed to find the effect of exogenous variables saving rate and labor growth rate on per capita GDP. Further, the model is extended by adding human capital as regressor. Data of 44 years of Nepali economy are used to analyze the model. Since time series of all the variables are stationary at first difference and they contain same stochastic trend, coefficients are estimated by using ordinary least square method. The analysis shows that the Solow model is applicable to Nepali economy as the predicted coefficients are very close to estimated coefficients. However, the estimated coefficients are very less than the predicted coefficients of the extended model. Furthermore, coefficient of labor growth rate is statistically insignificant in the extended model.